Enlightenment faith in human creative capacities - Drozdowicz, Zbigniew (Człowiek i Społeczeństwo, 2016)
In this article I present an argument for the thesis that one of the most significant revaluations of the Enlightenment was the creation and popularization of faith in the effective shaping of fate by man himself. In every example the Enlightenment had been referring to the creative possibilities of human reason. However, major differences occurred in understanding this very reason and its application in the praxis between the main representatives of the period. In my remarks I recall just a few of selected representatives of the English, Scottish and French enlightenment philosophy. The broadening of that list with other names, including the representatives of other nations, would allow probably to present much more diversified variants of this Enlightenment faith which since that period is a specific distinguishing mark of modernity.